Studi Komparatif Perlindungan Hukum dan Pengaturan Scalping Tiket Konser K-Pop di Indonesia dan Korea Selatan - Ghina Shofi Nabila; Setianingrum, Reni Budi (Universitas Muhammadiyah Yogyakarta, 2025)
The practice of purchasing tickets for resale at higher prices (scalping) is increasingly prevalent in Indonesia, but to date there are still no specific regulations, unlike South Korea, which has specifically regulated this practice. This research uses a quantitative approach with a normative-empirical comparative study, with data obtained from legal documents, official reports, and scientific literature. Based on this research, it can be concluded that there is a gap in legal protection between the two countries. South Korea has a more comprehensive regulatory system through explicit prohibitions in law and the use of technology in ticketing, which has been proven to significantly reduce scalping. In contrast, in Indonesia, regulations still do not provide adequate legal protection and specific provisions for ticket scalping. Indonesia needs to develop more specific regulations and implement a technology-based ticketing system to ensure fair access and consumer protection.